Consumer Preferences and Reactions to Brand Expansion - Vuković, Dijana; Kerum, Fani; Žukina, Miroslava (Naše gospodarstvo/Our economy, 2024)
Consumer purchasing power is one of the key determinants of consumer behavior, among other factors. Acceptance of new brands or product line extensions of existing brands is influenced by perceived value. New products can be added to existing product lines by introducing new products within them, or brands can expand horizontally by entering entirely new categories or product lines. Any vertical expansion, whether to a higher or lower level, comes after a price shift and a product quality achievement relative to its base product. While survey-based research provides valuable insights that support the growth of the Premium brand, building a strong relationship with customers, quickly identifying preferences, personalizing the offer and fostering a climate of trust remain its main sources of value. The purpose of the paper is to show the positive relationship that exists between the vertical growth of the brand and the increase in customer loyalty, as shown by the research conducted on a deliberate sample.